Legal Foundations of the Activities of Executive Authorities: European Integration Course - Drakokhrust, Tetyana (Actual problems of law (Aktual'ni problemi pravoznavstva), 2023)
This article examines and analyzes the legal principles that govern the activities of the executive authorities in Ukraine in the context of European integration. Key aspects, including transparency, public participation, adaptation of legislation, establishment of institutional mechanisms, monitoring and reporting, technical support, and others are discussed. The article emphasizes the importance of ensuring transparency and openness in the activities of government bodies to provide citizens with access to information and oversight of their work. Public participation and consultations are recognized as essential for the legitimacy and quality of decisions.The adaptation of legislation to European standards is considered a strategic step toward Ukraine's approximation to the European Union. The article also highlights the importance of creating specialized institutional mechanisms for the coordination and implementation of European integration tasks. Monitoring and reporting are recognized as crucial for tracking progress and ensuring accountability of government authorities to citizens and the international community. Technical support from European and international organizations is acknowledged as a vital resource for the implementation of European integration measures.In conclusion, the article underscores that adherence to these legal principles is critical for the successful process of Ukraine's European integration, which contributes to its development as a modern and democratic state.